The Impact of Labor Mobility on Living Standard: an Empirical Study on the Northern Region of Bangladesh - Faruque, Omar (i-Proclaim, 2021)
In the past 10 years, Bangladesh has experienced positive economic and social changes.  Historically, labor mobility has been a common livelihood strategy of the people as well as the Bangladeshi people. Labor mobility has become an integral part of the current global economy. The primary objective of this study is to provide a review of the impact of labor mobility on living standards in the northern region of Bangladesh. To develop the paper, primary as well as secondary data are collected. The quantitative, as well as qualitative analyses, are conducted in this study. Primary data is collected through a set of well-structured questionnaires. In the study, it is observed that there is 8% of labor are migrated within the last three years. From 2011 to 2015, the maximum laborers are migrated i.e., 37% and 33% migrated labor were day labor.  There are 35.56% of people with zero income level per day before their migration. On the other hand, after the migration, there are no people with nil income. Before the migration, 81.11% of people incur their expenditure for buying the inferior goods and the rest of the people incur for the necessary goods, but no one can consume the luxurious goods. On the other hand, after the migration, only 4.44% of laborers are availing of luxurious goods. So still they are not enjoying their life. Before the migration, they are 9% of people who are extremely dissatisfied with these types of facilities, and 33.33% of people were very dissatisfied. On the other hand, there are 23.33% of laborers are very pleased with their medical facilities, shelter, and child education facilities. The result shows that 41% of people are pushed for migration. It is assumed that there is a great impact of labor mobilization on the living standard. The labor is migrated in order to have a better living standard. There are two alternatives for their survival, first, we have to provide job opportunities near their residence, and the alternative is to provide a better living standard for the migrated people.